Association of initial recorded rhythm and underlying cardiac disease in sudden cardiac arrest. (January 2018) - Kauppila, Janna P.; Hantula, Antti; Kortelainen, Marja-Leena; Pakanen, Lasse; Perkiömäki, Juha; Martikainen, Matti; Huikuri, Heikki V.; Junttila, M. Juhani
Abstract: Background: Asystole (ASY) and pulseless electrical activity (PEA) are increasing and ventricular fibrillation (VF) or ventricular tachycardia (VT) declining as presenting rhythms of sudden cardiac arrest (SCA). Since there is limited information on possible differences in the etiology of underlying structural heart disease, we analyzed the clinical and/or autopsy findings of victims with ASY, PEA or VT/VF. Methods: All SCA cases with recorded ASY, PEA or VT/VF occurring after onset of witnessed collapse were analyzed by the emergency personnel between the years 2007–2012 within the Oulu University Hospital area. Underlying structural heart disease was diagnosed by medico-legal autopsy or by clinical investigation (echocardiography, angiography). Of a total number of 659 subjects with a documented rhythm at the time of SCA, 300 were determined to be due to cardiac disease at autopsy or as a result of clinical investigation. Delay was less than 30 min from collapse to rhythm recording in 274 subjects (mean age 65 ± 14 yrs; 214 males, 78.1%). Results: The presenting rhythm was ASY in 87 (31.8%) PEA in 38 (13.9%) and VT/VF in 149 subjects (54.4%). There was no significant difference in the delay from the onset of collapse to the rhythm recording between ASY (11 ± 8 min) and VT/VF (9 ± 6 min, p = 0.06) or PEA (6 ± 8 min) and VT/VF (p = 0.334). The majority of SCA subjects had an ischemic cause for the event (n = 216, 78.8%). Non-ischemic cause for SCA was associated with non-shockable rhythm (Non-ischemic: ASY 46.6% PEA 17.2% VT/VF 36.2% v. Ischemic: ASY 27.8% PEA 13.0% VT/VF 59.3%) even when adjusted for gender, age and delay from collapse to rhythm recording (ASY/PEA v. VT/VF, OR 3.2 95%CI: 1.67–6.50, p = 0.001). Conclusions: Asystole and PEA are a more common presenting rhythm than VT/VF at the time of SCA in non-ischemic cardiac disease. The decreasing trend of ischemic heart disease as a cause of SCA may partly explain the increasing trend of ASY/PEA.